Maternal alcohol use during pregnancy in a general national population in South Africa - Peltzer, Karl (S Afr J Psychiatr, 2019)
OBJECTIVE: Alcohol use in pregnancy is linked with various negative health effects on the infant. The aim of this study was to examine the prevalence of maternal alcohol use during pregnancy and socio-demographic and health correlates. METHODS: Data of ever-pregnant women from the cross-sectional ‘South African National Health and Nutrition Examination Survey (SANHANES-1) 2011–2012’ were analysed. The sample included 5089 adolescents and adult women aged 15–55 years. They responded to questions on alcohol use, socio-demographic and health indicators. RESULTS: The results indicated that 3.7% (95.0% confidence interval [CI] = 3.1, 4.5) of South African women had engaged in alcohol use during their pregnancy. In adjusted analysis, being mixed race, not employed, poor self-rated health status, ever been diagnosed with tuberculosis and having partial post-traumatic stress disorder were found to be associated with alcohol use during pregnancy. CONCLUSIONS: The study findings suggest links between socio-demographic and health variables and prenatal alcohol use, which may have public health policy implications.